Anesthetic Considerations in a Neonate Undergoing Thoracoscopic Removal of a Thoraco-Amniotic Shunt Following Prenatal Management of Fetal Pleural Effusion: A Case Report - Nugroho, Nugroho; Andi Ade Wijaya Ramlan (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2025)
Fetal pleural effusion is a condition characterized by the accumulation of fluid in the chest cavity of a developing fetus. It may be primary, often caused by lymphatic leakage such as chylothorax, or secondary to immune causes like Rh or ABO incompatibility, as well as nonimmune factors including chromosomal abnormalities, genetic disorders, infections, and congenital heart defects. These effusions may be associated with hydrops fetalis. The preferred prenatal treatment is thoraco-amniotic shunt (TAS), which drains pleural fluid into the amniotic sac. TAS improves lung development and has a survival rate of up to 85% in nonhydropic fetuses. A 34-week pregnant woman (gravida 2, para 1) was referred with suspected fetal lung fluid and diagnosed with fetal pleural effusion by ultrasound. After multidisciplinary evaluation, an ultrasound-guided thoraco-amniotic shunt (TAS) was performed under maternal spinal anesthesia, with fetal analgesia and paralysis achieved using fentanyl and vecuronium. The procedure was successful without complications. The patient delivered by cesarean section at 38 weeks. Postnatal imaging showed the shunt in place without residual effusion. On day six of life, the neonate underwent successful thoracoscopic shunt removal under general anesthesia, with stable intraoperative and postoperative outcomes. Conclusion, Thoraco-amniotic shunt placement and postnatal thoracoscopic removal require careful anesthetic planning and multidisciplinary coordination. Understanding maternal-fetal physiology and neonatal immaturity is essential. With thorough assessment and precise anesthetic management, both intrauterine and neonatal procedures can be performed safely with favorable outcomes.